Therapeutic Plasma Exchange in the Management of Postpartum HELLP Syndrome: A Case Report - Parul Jaiswal; Prashant Suryarao; Dipak Kolate (Journal of Clinical and Diagnostic Research)
Haemolysis, Elevated Liver enzymes and Low Platelet count (HELLP) syndrome is a serious obstetric complication occurring during pregnancy or postpartum. It often co-exists with other Thrombotic Microangiopathies (TMAs), including atypical Haemolytic Uraemic Syndrome (aHUS). Differentiating between these conditions is crucial due to varying treatment approaches. Postpartum aHUS, a rare but potentially fatal condition, involves unchecked complement activation leading to severe renal failure, hypertension and microangiopathic haemolysis. A multidisciplinary approach and early diagnosis are vital for optimal patient outcomes. A 29-year-old woman presented on postoperative day 1 after an emergency Lower Segment Caesarean Section (LSCS) with oedema, proteinuria, hypertension, sudden visual impairment and persistent abdominal pain. Laboratory findings suggested HELLP syndrome with concurrent postpartum aHUS (decreasing platelet count, increased liver enzymes, decreased renal function and microangiopathic haemolysis). Critical care management included intravenous fluids, antihypertensives, antibiotics and analgesics. Therapeutic Plasma Exchange (TPE), initiated due to TMA and severe renal impairment, significantly improved clinical outcomes. Haematological issues were addressed with corticosteroid therapy (initially intravenous methylprednisolone, gradually transitioned to oral prednisolone). Diuretics managed fluid control and close monitoring continued. The patient was discharged with supportive treatment, controlled hypertension and stable renal function. This case highlights the importance of early detection and a tailored multidisciplinary approach in managing postpartum HELLP syndrome with aHUS. Further research is needed to improve diagnostic algorithms and treatment plans due to overlapping clinical presentations.